Golden Gate Club of San Francisco barbecue - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
The Golden Gate Club of San Francisco poses for a group picture during a barbecue at Dr. Ada Scott Morton's home in San Jose, California. Dr. Ada Scott Morton was a prominent surgeon in San Jose. A majority of the children sit around a table together in the foreground. Food servers pose with food and pitchers.